SADAATURYA VIS-A-VIS LIFESTYLE DISORDERS - Shenoy Savitha . K. R (International Journal of Applied Ayurved Research, 2017)
“Life” is the duration between birth and death of an individual. This period would be most enjoyable if the body stayed in a healthy state. But today, the lifestyle has become such that people are seldom healthy, thus making life more of a burden. This article aims at understanding the concept of Sadaaturya told in Ayurveda, in light of lifestyle disorders which are most spoken off today. Not only will the article dive into understanding of this concept, but also, enlist the possible solutions in the form of Life style Management.